Combined hepatoprotective and antidepressant effects of resveratrol in an acute model of depression - Rania F. Ahmed; Rehab Fawzy Abdel-Rahman; Omar A.H.A. Farid; Salma A. El-Marasy; Alyaa F. Hessin (Faculty of Pharmacy, Cairo University, 2014)
There are numerous herbal medicines that have been introduced into psychiatric practice because of greater compliance and milder side effects. Polygonum cuspidatum is a native Asian plant; known for its medicinal properties and traditionally used in the treatment of neuropsychiatric disorders, such as psychosocial stress, dementia and Parkinson's disease. Resveratrol is the active ingredient of P. cuspidatum. Researchers have suggested that the trans-isomer of resveratrol demonstrates a variety of pharmacological activities including antioxidant, anti-inflammatory, hepatic and neuroprotective properties. In this study we examined the hepatoprotective and antidepressant effects of trans-resveratrol against fluoxetine in an acute reserpine model of depression in rats. Main methods: depression-like behaviors were induced by single reserpine intraperitoneal injection (6 mg/kg, i.p.). Trans-resveratrol (15, 30 and 60 mg/kg bwt) and fluoxetine (24 mg/kg bwt) were administered orally for the following 3 days. Behavioral effects namely open field test (OFT) and forced swimming test (FST) and biochemical parameters namely neurotransmitters levels and antioxidant contents were assessed. Liver histopathological examination was performed. Key findings: Results revealed that resveratrol (60 mg/kg bwt) showed a potential hepatoprotective and an antidepressant-like effects compared to those of fluoxetine.